Miami police file : the O'Nell case - Clemen, Gina D. B.; D'Altan, Paolo (Genoa [Italy] : Black Cat, 2007)
Three teens set out to investigate the mysterious disappearance of their teacher Peter O'Nell in the Burmuda Triangle and encounter ghostly appearances and clues that lead them to the wax museum, O'Nell's old home, and a millionaire's yacht. Contains CD-ROM with games and activities.
"Step one, A2"--Cover.
Enhanced compact disc.
Young Adult
System requirements stated.
Keywords: Readers; CD-ROMs.; Compact discs; Reading materials; CD-ROMs.; Compact discs